National Survey of Families and Households (NSFH): Wave III, 2001-2002 - Bumpass, Larry L. ([Verlag nicht ermittelbar], 2006)
National Survey of Families and Households (NSFH), a longitudinal population-based survey of families and households in the United States, investigates the causes and consequences of changes in American family and household structure. The first wave, NSFH Wave I, consists of interviews conducted during 1987-1988 with a national probability sample of 13,017 male and female primary respondents. Several population groups are oversampled, including minorities, single parents, persons with step-children, cohabitating persons, and recently married persons. In addition to each primary respondent questionnaire, there was a questionnaire for the spouse or partner of the primary respondent, if applicable, and detailed information was collected about a focal child. Respondents were followed up during 1992-1994, five years after the initial interview. NSFH Wave II included personal interviews with both the original respondent and the respondent's partner (including the previous partner if the original union had dissolved), telephone interviews with the focal child, and telephone interviews with a randomly selected parent of the original respondent. (Both NSFH Wave I and NSFH Wave II are available from ICPSR. See NATIONAL SURVEY OF FAMILIES AND HOUSEHOLDS, WAVE I, 1987-1988, AND WAVE II, 1992-1994 [ICPSR6906].) The current study, NSFH Wave III, is the third follow up and was conducted in 2001-2002. The sample included all NSFH Wave I main respondents and spouse/partner with focal child eligible for the NSFH Wave II interviews, interviews with these focal children (now ages 18-34), and all other NSFH Wave I main respondents ages 45 and over in 2000, as well as their NSFH Wave I spouse/partner. NSFH Wave III data are not currently available through ICPSR. The data can be accessed from the National Survey of Families and Households website at the link listed below.